LA EDUCACIÓN DEL CIUDADANO EN EL CONTEXTO ILUSTRADO: EL ECO DE HOLBACH EN ESPAÑA - Francisco Sánchez-Blanco (Cuadernos de Ilustración y Romanticismo)
The secularization of thought includes the purpose of educating for coexistence in a political framework different from the feudal regime. Moral theology is replaced by a civil morality. In Spain this change in orientation can be detected thanks to the influence of the radical Enlightenment that develops in France in the second half of the 18th Century.